Molecular weight of fucoidan governs its interaction with ovalbumin: Multi-scale insights into complex formation, structural alteration, and binding mechanism - Yingmei Wu; Yingying Sun; Longquan Xu; Fang Geng; Xin Li; Chao Ai; Lei Chen; Yan Zhou; Peng Luo; Qun Huang (Food Hydrocolloids, 2026)

Rapid detection of maize seed vigor via multi-branch interpretable deep learning integrated with multimodal data fusion optimized by environmental factors - He Li; Yilin Mao; Ruisha Xie; Hongtao Shi; Han Zhang; Yinlin Chen; Xuelei Yang; Riliang Gu; Sun Qun (Computers and Electronics in Agriculture, 2026)

Contribution of the slab fluids- melts to petrogenesis of adakitic rocks related to gold mineralization: Mo isotopic constraints - Shu-wen Li; Wen-liang Xu; Qun Yang; Yun-sheng Ren; Wu-shuang Zhang; Bin Wang; Kan Gao; Si-tong Chen; Yao-heng Fang; Hao-zhe Li; Tian-ci Liu; Xuan-mei Xue; et al. (Lithos, 2026)

Direct, catalyst-free H2O2 synthesis via scalable plasma reactor - Dongxing Li; Shao-Pei Wang; Qun Chen; Shengyan Meng; Zhaojun Zhang; Jintao Sun; Shu Liu; Cun-Feng Cheng; Qi Chen; Shui-Ming Hu; Dong H. Zhang; Annemie Bogaerts; et al. (Chemical Engineering Journal, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Activity-guided discovery of antibiotic-transforming bacteria from environmental microbiomes using D-amino acid–assisted fluorescence-activated cell sorting - Yi Liu; Kai-Li Wang; Yu-Qi Hong; Ye Yuan; Hua Wang; Yi-Qun Chen; Sheng-Song Yu; Zi-Xuan Lu; Yuan Pan; Ting-Ting Zhu (Environmental Pollution, 2026)

Manipulating the organic-salt selectivity of N-2-hydroxyethylpiperazine based poly-ester-amide (PEA) membranes for antibiotic-NaCl separation - Qinghua Guo; Tao Shi; Lu Dai; Zhiguo Yan; Qun Chen; Man Xu; Yanbo Li (Desalination, 2026)

A self-crosslinking powder based on carboxymethyl chitosan and guar gum with free radical scavenging for rapid hemostasis and promotion of wound healing - Zheng Chen; Jiawei Shen; Bin Zuo; Shuohua Gu; Kaiyue Xu; Yingping Li; Qun Wang; Yilin Wang; Jiulong Zhao; Shige Wang (Carbohydrate Polymers, 2026)

Solar-driven photothermal activation of peroxydisulfate for ethyl xanthate removal and reuse of mineral processing wastewater - Haoran Song; Jinyi Wu; Lechen Ren; Pu Wang; Canhai Shi; Xuewei Hu; Chen Li; Qun Zhao; Senlin Tian (Process Safety and Environmental Protection, 2026)

Exogenous calcium modulates oxalic acid metabolism via repression of LcAAE3 and mediates calcium accumulation in litchi pericarp and fruit pedicel - Dong-Cheng Li; Zhi-Qun Zhong; Teng-Kai Chen; Yi-Tong Liu; Yue-Han Sun; Hui-Cong Wang; Ren-Fang Zeng; Xu-Ming Huang (Journal of Plant Physiology, 2026)

Correlation of hydrophilicity and active N sites with organic iodine adsorption in covalent organic frameworks - Si-Yu Chen; Shuai Wang; Nai-Xin Zhang; Peng-Cheng Zhang; Wei-Qun Shi; Li-Yong Yuan (Journal of Hazardous Materials, 2026)

Dscam alternative splicing tunes intestinal immunity and microbiota homeostasis in the Chinese mitten crab - Zifeng Wang; Chengyu Lv; Jinming Chen; Kaimin Zhou; Qun Wang; Youting Zhu; Weiwei Li (Fish & Shellfish Immunology, 2026)

Vibration isolation for mechatronic metamaterial rings with piezoelectric shunting circuits - Long Zhao; Ze-Qi Lu; Li-Fang Lin; Hu Ding; Li-Qun Chen (Engineering Structures, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Hair Follicle Stem Cells: Emerging Physiology and Therapeutic Applications - Shuyuan Yang; Qun Chen; Hanluo Li; Guang Yang (Stem Cell Reviews and Reports, 2026)

Stratified Reference Intervals for Serum Selenium by Selenium Environment, Health, and Physiological Status in Populations from Shaanxi Province, China - Zhe Yang; Xianshun Gao; Meng Qu; Xiaoping Du; Hui Xie; Xiaohong Li; Rongli Lian; Chen Chen; Qun Chen (Biological Trace Element Research, 2026)

A specific integrin αPS3βPS1 heterodimer is required for hemocyte phagocytosis in Chinese mitten crab, Eriocheir sinensis - Rongping Wang; Chengyu Lv; Junfeng Hou; Jinming Chen; Chaohui Xu; Kaimin Zhou; Weiwei Li; Qun Wang; Youting Zhu (Fish & Shellfish Immunology, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Houpu Sanwu decoction alleviates rat intraperitoneal adhesion by regulating macrophage polarization and inhibiting inflammatory responses - Mei Liu; Quanxin Chen; Yan Cui; Tianming Wang; Qun Li; Zhihang Wu; Richeng Li; Yuan Tang; Haibang Pan (Tissue and Cell, 2026)

Deep visual multi-omics reveals intra-tumor heterogeneity of gene expression and immunophenotype in colorectal cancer - Shijun Lei; Wanshan Ning; Hongyan Zhang; Qun Chen; Luming Xu; Shaobo Tian; Xiaoqiong Li; Wenyu Liu; Mengxi Xiang; Feng Liu; Guobin Wang; Lin Wang; et al. (Science Bulletin, 2026)

Static and dynamic responses of a novel UEST column under axial compression and wave force - Yun-Long Chen; Jing-Zhong Tong; Li-Sen Zheng; Chao-Qun Yu (Ocean Engineering, 2026)

Transcriptomic reprogramming underlies melatonin-mediated enhancement of cadmium tolerance and lateral root growth in soybean - Rongrong Li; Jinming Kou; Xiaoqiong Liu; Hengrui Dai; Ze Liu; Qun Chen; Tanveer Ahmad Khan; Xinjia Wang; Yanli Chen; Qi Chen; Xiaojun Pu (Journal of Hazardous Materials, 2026)

Beyond supporting electrolytes: Novel solid polymer electrolyte system for enhanced electrochemical degradation of imidacloprid wastewater - Chen Li; Yunfeng Yang; Zhenzhen Wang; Jianfei Wang; Xinyu Song; Xiangfen Cui; Haoran Song; Qun Zhao; Shugen Liu; Senlin Tian (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Ultra-sensitive gas sensor enabled by architectural and electronic synergy in bio-templated ZnO/hollow carbon microtubules” [J. Environ. Chem. Eng. 14 (2026) 121787] - Chuanxi Li; Shengxi Chen; Bing Gao; Yueheng Niu; Bo Ran; Yibo Han; Zhaofeng Wu; Ning Tian; Qun Jing (Journal of Environmental Chemical Engineering, 2026)

Decoupling of Fe isotope and Fe3+/ΣFe in arc igneous rocks: Implications for crustal metasomatism and its contribution to mantle redox - Li-Tao Ma; Li-Qun Dai; Zi-Wei Yao; Zi-Fu Zhao; Ye-Dan Hu; Zhen-Wu Chen; Guo-Chao Sun (Geochimica et Cosmochimica Acta, 2026)

Robust and multifunctional PDMS/MOF-engineered fabrics with superior water repellency, UV shielding, and EMW absorption - Kaiying Zhao; Qun Wang; Fangying Guo; Minji Kwon; Shengyou Li; Weihong Gao; Tianxiao Chen; Guangtao Zan; Binjie Xin (Chemical Engineering Journal, 2026)

Engineered Escherichia coli Nissle 1917 carrying D-lactate dehydrogenase suppresses glioblastoma malignancy via gut-brain axis reprogramming - Qun Cao; Jiazheng Wang; Xuxiu Lu; Zhuo Li; Chenghui Guo; Chuanke Hou; Ping Li; Anjing Chen (Chemical Engineering Journal, 2026)

Molybdenum isotopes in metamorphic and magmatic rocks may record substantial fluid activity in continental subduction zones - Wei Fang; Li-Qun Dai; Ren-Xu Chen; Zi-Fu Zhao (Chemical Geology, 2026)

Dual Low-b-value-driven U-shaped fusion GAN for synthesizing high-b-value prostate DWI - Rui Feng; Qun Huang; Aiping Chen; Chuanbing Wang; Leilei Zhou; Jingjing Xu; Xiaodong Wang; Da Cao; Xiuhan Li; Wei Wang (Physical and Engineering Sciences in Medicine, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

The expanding world of plant NLR pairs - Cheng-Wei Sang; Yan-Mei Zhang; Sai-Xi Li; Jian-Qun Chen; Zhu-Qing Shao (Trends in Plant Science, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Release of cadmium, lead and zinc from surface soil to the atmosphere via wind erosion at medium-low wind speeds - Qiuye Zhang; Hongyan Liu; Fang Liu; Xuexian Li; Zhe Li; Weijie Chen; Qun Zhao (Atmospheric Pollution Research, 2026)

Anti-asthmatic effects and ingredient annotation of the active fraction from Ganoderma lucidum - Ning Li; Qian He; Cunwu W. Chen; Qun Zhao; Yanfei F. He (Journal of Natural Medicines, 2026)

Ultra-sensitive gas sensor enabled by architectural and electronic synergy in bio-templated ZnO/hollow carbon microtubules - Chuanxi Li; Shengxi Chen; Bing Gao; Yueheng Niu; Bo Ran; Yibo Han; Zhaofeng Wu; Ning Tian; Qun Jing (Journal of Environmental Chemical Engineering, 2026)

Transforming steel slag into a soil-like matrix via CO2 sequestration: A strategy for simultaneous waste valorization and carbon emission reduction - Xin Xie; Chen Li; Zhiyuan Ma; Ludan Zhang; Qun Zhao; Jie Li; Senlin Tian; Kebin He (Journal of Environmental Management, 2026)

Activation of peroxymonosulfate by MXene-confined micron-sized copper particle catalyst: A new understanding of size effects - Haoran Song; Xudong Zhang; Mengting Guo; Pu Wang; Jie Li; Chen Li; Yan Cao; Linfeng Zhang; Qun Zhao; Xuewei Hu; Senlin Tian (Chemical Engineering Journal, 2026)

Feasibility of the constructed Technosols prepared solely from concrete recycled aggregates as a plant growth medium - Fengrui Zi; Qun Zhao; Haiyan Chen; Zhangqian Wu; Wenxing Li; Haoran Song; Jianhong Huang; Jie Li; Xuewei Hu; Senlin Tian (Journal of Soils and Sediments, 2026)

Differential enrichment mechanisms of organic matter in middle-upper Triassic lacustrine mudstone, north Kuqa depression (Tarim Basin, China): An integrated approach utilizing inorganic and organic geochemical evidence - Dejiang Li; Qun Zhao; Lingyu Zhao; Yanpeng Chen; Ze Deng; Xiangchun Chang; Bingbing Shi; Runye Han; Shangbin Wang (Acta Geochimica, 2026)

Whole-genome and microbial diversity analyses reveal mechanism of GY8 for enhancing cadmium removal rate of duckweed - Mi Zhang; Yu-Ting Liu; Xiang-Qin Li; Zhi-Qun Chen; Yan Lan; Ai-Juan Tan; Gui-Li Yang (International Biodeterioration & Biodegradation, 2026)

Life cycle perspective on biochar-catalyzed co-pyrolysis of biomass and plastic waste across multiple treatment scenarios - Qun Wang; Zhuo Li; Zhiwei Wang; Gaofeng Chen; Na Guo; Xuege Li; Tingzhou Lei (Bioresource Technology, 2026)

The relationships between the main root morphological characteristics and biomass allocation of Ageratina adenophora along the Qionghai lakeside, western Sichuan Plateau, China - Qun Li; Yu-Mei Qiu; Lan Chen; Cheng-Zhang Zhao; Bo Li; Hong Yang (Plant and Soil, 2026)

Screening of quorum Sensing-Dependent strong promoters in Pseudomonas bijieensis 2P24 for metabolic optimization and Recombinant protein production - Jie Li; Hongguang Ma; Na Tai; Yue Fan; Mengxue Nie; Xuanying Tao; Zhilin Wang; Jinxin Wang; Xiangpeng Deng; Cheng Shen; Xuanxuan Chen; Jin Wang; et al. (World Journal of Microbiology and Biotechnology, 2026)

Mitophagy Inhibition Suppresses Seizures in Status Epilepticus Mice by Decreasing Hippocampal NLRC4 Expression - Zhi-Cheng Dong; Min Liu; Jin-Yi Zhou; Li-Qun Geng; Mei Li; Xu-Qin Chen (Journal of Molecular Neuroscience, 2026)

Estimating sea surface height signatures of internal solitary waves and their application to SWOT observations - Tao Xu; Xiao He; Xu Chen; Qun Li; Jing Meng (Ocean Engineering, 2026)

Decarbonizing fossil-to-chemicals conversion: reliable real-time optimization under coupled chemical and carbon capture dynamics - Zhibo Zhang; Ze Li; Mengzhen Zhu; Yani Wang; Yibo Yuan; Honghua Qin; Jiarong Lu; Yaqian Li; Xin Zhou; Yibin Liu; Qun Zhang; Hao Yan; et al. (Journal of Cleaner Production, 2026)

The m6A methyltransferase METTL3 regulates antimicrobial peptide expression via the Toll pathway in Eriocheir sinensis - Jinming Chen; Yang Li; Qingding Hao; Chaohui Xu; Guoqin Sheng; Kaimin Zhou; Weiwei Li; Qun Wang; Youting Zhu (Fish & Shellfish Immunology, 2026)

Corrigendum to “Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression” [Chem. Eng. J. 527 (2026) 171844/ CEJ_171844] - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

The promoter sequence of (-)-limonene synthase in Mentha Canadensis and its strong activity in the glandular trichome and in the stomatal guard cells - Shumin Li; Zhichao Xue; Taolan Xiao; Xiwu Qi; Hailing Fang; Li Li; Yang Bai; Dongmei Liu; Qun Liu; Zequn Chen; Xu Yu; Chengyuan Liang (Acta Physiologiae Plantarum, 2026)

Catalytic co-pyrolysis of rice straw and polystyrene for selective production of monocyclic aromatic hydrocarbons - Na Guo; Zhiwei Wang; Ruijie Liu; Huina Zhu; Gaofeng Chen; Xueqin Li; Qun Wang; Hongxun Zhang; Tingzhou Lei (Process Safety and Environmental Protection, 2026)

Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

The Reorganization of Cerebellar Functional Network Topology in Post-stroke Aphasia: A Resting-State fMRI Study - Liting Chen; Zhenye Luo; Wenfeng Mai; Xiaoling Wu; Xiaole Fan; Lifeng Li; Yongqiang Shu; Xiaoyun Chen; Qun Fang; Hong Wang; Yanhong Dai; Shuixing Zhang (Molecular Neurobiology, 2026)

Aggregate size mediates the stability and temperature sensitivity of soil organic carbon in response to decadal biochar and straw amendments - Yalan Chen; Yakov Kuzyakov; Qiwen Ma; Zhangliu Du; Ke Sun; Keqing Xiao; Xinru Liang; Yang Li; Yunxian Zhang; Xianqiang Lai; Wei Fu; Bo Gao; et al. (Soil Biology and Biochemistry, 2025)

Evaluating the impact of battery electric vehicle and hydrogen fuel cell vehicle deployment on emissions in China's light-duty passenger vehicle fleet: A scenario-based well-to-wheel analysis - Qun Wang; Xuege Li; Mianqiang Xue; Zhiwei Wang; Yongzhi Liu; Gaofeng Chen; Xinxin Wang; Na Guo (Journal of Cleaner Production, 2025)

Coupled deep electrical resistance heating and shallow permanganate oxidation for indoor remediation of chlorinated hydrocarbons in layered soils - Yutian Chen; Xiang Wang; Qun Li; Yuanchao Zhao; Tingting Fan; Junzeng Xu; Shengtian Zhang; Decheng Jin; Jinzhong Wan (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

A comparative study highlights superiority of LSTM in crop genomic prediction - Ruiqing Pan; Yaolong Yang; Yuanyuan Zhang; Qun Xu; Yue Feng; Junyu Chen; Wei Li; Shoupu He; Xinghua Wei; Mengchen Zhang (Planta, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Investigation on hydro-mechanical coupling shear creep properties of jointed rock masses - Qun Sui; Weizhong Chen; Luyu Wang; Hui Li (Tunnelling and Underground Space Technology, 2025)

Sustainable thermochromic coatings for pavement cooling and carbon offset under climate change - Yujing Chen; Aimin Sha; Wei Jiang; Wenxiu Jiao; Yangsen Cao; Xinzhou Li; Xiaotong Du; Kui Hu; Qun Lu (Transportation Research Part D: Transport and Environment, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Unraveling ozone formation sensitivity to ambient VOCs and NOx at urban and mountain sites in a typical city of eastern China - Xiaorong Zhang; Deming Han; Jiandong Shen; Feng Chen; Liuyan Cao; Jinhan Chen; Xu Lin; Yang Yang; Lin Yang; Wenjing Li; Xiaowei Qiao; Shuangxu Zhou; et al. (Environmental Pollution, 2025)

Analysis and optimization of a quasi-zero-stiffness vibration isolator based on partially rigidized compliant mechanisms - Zhi-Qiang Zhang; Mu-Qing Niu; Li-Qun Chen (Engineering Structures, 2025)

ZWINT down-regulated by miR-495-3p inhibited lung metastasis of breast cancer by blocking p38 MAPK signaling pathway activation - Ming-tao Shao; Wei-wen Li; Yong Li; Ping Chen; Shuai-shuai Yu; Wen-jie Lu; Chun-mei Chen; Yan Dong; Yi-wen Zhang; Qun-chen Zhang (Human Cell, 2025)
Breast cancer metastasis is the primary cause of patient mortality, yet effective therapeutic targets remain limited. Building on our prior identification of ZWINT as a prognostic marker linked to metastasis, this study defines its critical functional role and regulatory mechanism. Multi-omics analysis revealed a strong association between ZWINT expression and metastatic processes across breast cancer subtypes. Functionally, ZWINT knockdown significantly inhibited breast cancer cell migration and invasion in vitro and dramatically reduced lung metastasis in vivo. Mechanistically, we discovered that miR-495-3p directly targets and suppresses ZWINT expression, and this miR-495-3p/ZWINT axis acts through inhibiting p38 MAPK pathway activation to suppress metastatic progression in vitro. Our findings demonstrate that ZWINT drives breast cancer metastasis and is negatively regulated by miR-495-3p. The newly identified miR-495-3p/ZWINT/p38 MAPK axis may provide a promising therapeutic target for suppressing breast cancer progression.

Characterization of the Lonicera japonica R2R3-MYB transcription factor gene LjaMYB305 that promotes the flavonoid biosynthesis - Hailing Fang; Yan Wan; Huiping Liu; Xiwu Qi; Xu Yu; Zequn Chen; Qun Liu; Li Li; Yang Bai; Dongmei Liu; Chengyuan Liang (Plant Science, 2025)

Optimization of green development for methylene diphenyl diisocyanate industry based on synergistic benefit - Qun Shen; Qianqian Chen; Li Shang; Nannan Sun; Jiaming Gu; Tao Li; Hongbei Wang; Weisheng Yu; Xuehang Song; Wei Wei (Journal of Environmental Chemical Engineering, 2025)

Enhanced denitrification by bio-cathodes in the treatment of aquaculture wastewater in microbial electrochemical systems - Qun Li; Sirapat Khodseewong; Boyang Chen; Takashi Sakamaki; Haochi Zhang; Xian Cao (Journal of Environmental Chemical Engineering, 2025)

Myxomycetes in urban green space in subtropical China: Spatiotemporal patterns override forest type effects - Wen-Long Song; Di Lin; Min-Li Cai; Xia Chen; Qun Dai; Shuang-Lin Chen (Fungal Biology, 2025)

Discovery of a novel DNA aptamer for impeding tumor metastasis by blocking the functional activity of target protein on exosome - Qun Wang; Ziwei Miao; Shihan Sun; Yinuo Ma; Zhezhou Chen; Yanxi Li; Wei Ba; Menghu Liang; Jin Fang; Wanming Li (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Climate-adaptive windcatcher natural ventilation integrated with passive and low-energy technologies: A review of current and future developments - Jiaxiang Li; John Calautit; Carlos Jimenez-Bescos; Wenjie Song; Saffa Riffat; Qun Chen (Building and Environment, 2025)

Evolution of MJO structures during eastward propagation - Yuqing Long; Jian Ling; Chongyin Li; Guiwan Chen; Guanshun Zhang; Qun Tian; Lina Huang; Yu Zhu (Theoretical and Applied Climatology, 2025)

Invasion legacy weakens the positive effect of plant genotype diversity on soil multifunctionality - Wei Song; Cai Cheng; Zekang Liu; Shumeng He; Shenggui Xue; Xue Chen; Jingru Zhang; Lejie Wu; Qun Zhang; Guiyao Zhou; Yann Hautier; Ruiting Ju; et al. (Plant and Soil, 2025)

Mitochondrial GPATs protect Arabidopsis from water stress by impacting cuticle and secondary cell wall development - Qianru Jia; Yang Bai; Shujuan Zhang; Li Song; Hongmei Zhang; Wei Zhang; Qiong Wang; Xiaoqing Liu; Xin Chen; Qun Zhang; Huatao Chen (Plant Cell Reports, 2025)

Endophytic Bacterium Paenibacillus illinoisensis Y11 Promotes Duckweed Growth and Enhances Cadmium Pollution Remediation - Zhi-Qun Chen; Ai-Juan Tan; Yi-Fei Wan; Yu-Han Dong; Xiao Yang; Gui-Li Yang (Current Microbiology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Growth-promoting bacterium Enterobacter sp. CS8-gfp triggers jasmonate signaling pathway for atrazine and thiamethoxam degradation in rice (Oryza sativa L.) - Li Ya Ma; Qun Wan; Jing Ge; Yong Li; Fayun Feng; Mei Li; Jinjin Cheng; Jian Chen; Ya Wang; Yaoyao Cao; Chenye Yang; Xiangyang Yu (Journal of Cleaner Production, 2025)

Insight into interaction among soil microbial community, soil metabolomics and enzyme activity after long-term PAH stress - Liping Zheng; Qun Li; Junyang Du; Xiaosong Lu; Tingting Fan; Li Xu; Heidi qunhui Xie; Yangsheng Chen; Bin Zhao (Journal of Environmental Sciences, 2025)

A novel multimodal computer-aided diagnostic model for pulmonary embolism based on hybrid transformer-CNN and tabular transformer - Wei Zhang; Yu Gu; Hao Ma; Lidong Yang; Baohua Zhang; Jing Wang; Meng Chen; Xiaoqi Lu; Jianjun Li; Xin Liu; Dahua Yu; Ying Zhao; et al. (Physical and Engineering Sciences in Medicine, 2025)

Targeted discovery of oxygen-bridged sesquiterpenes from Cinnamomum migao by MS/MS-based molecular networking and their neuroprotective activities - Lang Zhou; Xiong Pan; Fa-ju Chen; Mei Peng; Yu Wang; Ming Gao; Li-shou Yang; Liang-qun Li; Juan Yang; Xiao-sheng Yang; Qi-ji Li (Phytochemistry, 2025)

Remediation of lead and arsenic co-contaminated soils using self-sustaining smoldering: Performance and mechanism - Jie Li; Haiyan Chen; Fengrui Zi; Zhangqian Wu; Xiangfen Cui; Haoran Song; Jianhong Huang; Qun Zhao; Xuewei Hu; Senlin Tian (Journal of Environmental Chemical Engineering, 2025)

Dual-mode superhydrophobic composite film for temperature regulation, stable thermoelectric output enhancement, and physiological movement monitoring - Hui-Di Wang; Chao-Hua Xue; Xinyang He; Yan Yang; Zhan-You Ji; Chao-Qun Ma; Li Wan; Yong-Gang Wu; Meng-Chen Huang; Xiao-Jing Guo (Chemical Engineering Journal, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Diffusion-driven zircon Zr isotopic fractionation during ultramafic–mafic magmatic differentiation - Li-Tao Ma; Li-Qun Dai; Shao-Bing Zhang; Ren-Xu Chen; Qiong-Xia Xia; Zi-Fu Zhao (Geochimica et Cosmochimica Acta, 2025)

Corrigendum to “Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis” [Toxicology and applied Pharmacology, 2023, 462:116415] - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2025)

Simultaneous and instrument-free detection of quinine and crystal violet based on a dual-emissive Eu3+-functionalized metal-organic framework - Hou-Qun Yuan; Yuan Yuan; Si-Yi Liu; Jia-Hao Fu; Yi-Fan Xia; Wei Li; Meng-Yuan Pan; Lirong Jiang; Peiyao Chen; Guang-Ming Bao (Journal of Hazardous Materials, 2025)

Atmospheric CO2 and CH4 observations in Hangzhou before, during, and after the 2023 Asian Games: Insights from vehicle-carried and fixed stations - Tianhao Wang; Jiansen Wang; Ning Hu; Ruonan Li; Meng Shan; Qun Lin; Longlong Chen; Jun Wang; Yuxin Jiang; Zhonghao Yang; Wei Xiao (Atmospheric Pollution Research, 2025)

Chermesins I-N: Bioactive spiromeroterpenoids from the marine-sourced fungus Penicillium chermesinum AS-400 - Yi-Wei Liu; Xue-Yi Hu; Xiao-Dan Chen; Xiao-Ming Li; Sui-Qun Yang; Hong-Lei Li; Bin-Gui Wang (Phytochemistry, 2025)

Differences in starch and protein composition, morphological and structure, and their impacts on eating quality of soft japonica rice under different light and nitrogen fertilizer conditions in southern China - Zhongtao Ma; Jianghui Yu; Xi Chen; Jiale Cao; Ying Zhu; Guodong Liu; Guangyan Li; Fangfu Xu; Qun Hu; Hongcheng Zhang; Haiyan Wei (Food Chemistry, 2025)

Association of greenness exposure with serum vitamin D status and effects of ambient particulate matter among pregnant women in early pregnancy - Dongjian Yang; Yanling Shen; Qun Wang; Xin Sun; Mengxiang Li; Jinjing Shi; Lei Chen; Jun Zhang; Xinhua Ji (Environmental Pollution, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Comprehensive assessment, intelligent prediction, and precise mitigation strategies for greenhouse gas emissions in full-scale wastewater treatment plants - Zitan Zhang; Fei Qi; Yao Liu; Muhammad Bilal Asif; Amir Ikhlaq; Zhenbei Wang; Caocao Chen; Chen Li; Jing Chang; Qun Li; Ye Li; Yujie Li; et al. (Environmental Research, 2025)

The Drainage Dysfunction of Meningeal Lymphatic Vessels Is Correlated with the Recurrence of Chronic Subdural Hematoma: a Prospective Study - Jiahao Zhang; Lei Yu; Xiaoyu Wang; Qian Yu; Bingrui Zhu; Haocheng Zhang; Yibo Liu; Huaming Li; Anke Zhang; Kaikai Wang; Yezhao He; Qun Wu; et al. (Translational Stroke Research, 2025)

Efficacy and safety of combined anti-vascular and two-staged stereotactic radiosurgery therapy for brain metastases with brainstem compression: a retrospective multicenter study - Zhu Xiuming; Zhou Jia; Chen Qun; Chen Haining; Li Renli; Zhu Yucun; Wang Zheng (Clinical & Experimental Metastasis, 2025)

Potential mechanisms of ZiGongDing in treating HPV-induced cervical intraepithelial neoplasia: a network pharmacology and experimental verification study - Li Wan; Kan Chen; Xiaorong Ma; Lu Han; Qun Xie; Lihong Wang; Xinmei Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Differential contribution of Cu2+ and OH− to the formation of Nε-carboxymethyllysine and Nε-carboxyethyllysine in preserved egg white during pickling - Le Chen; Zhuosi Yu; Shiqin Dong; Zixiao Li; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

Exposure engineering of active sites of Co-N-C for efficient oxygen reduction reaction - Ting Chen; Chao Hao; Zhenyu Chen; Jiawang Li; Changqing Lin; Pei Kang Shen; Zhi Qun Tian (Chemical Engineering Journal, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Bipolaristeroid A, a 5,6-seco-9,10-seco-steroid with cytotoxic activity from the fungus Bipolaris maydis - Yong Shen; Lianghu Gu; Qun Zhou; Xiaotian Zhang; Mengru Yu; Qin Li; Yu Liang; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2025)

Transparent mechanism of salted egg (white) hierarchically and synergistically driven by NaCl, NaOH and thermal treatment: Based on empirical data and molecular simulation - Le Chen; Shiqin Dong; Peng Xu; Zhuosi Yu; Yating He; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

Phenolic acid-containing compounds enhanced Fe3+/peroxides processes for efficient removal of sulfamethoxazole in surface waters - Zhenzhen Wang; Xiaolei Jia; Jianfei Wang; Chen Li; Haoran Song; Qun Zhao; Yingjie Li; Senlin Tian (Environmental Research, 2025)

A compliant helical structure to amplify inertia for nonlinear vibration absorption - Jun-Jie Huang; Mu-Qing Niu; Yimin Fan; Li-Qun Chen (Engineering Structures, 2025)

Pyridoxine supplementation before puberty ameliorates MAM-induced cognitive and sensorimotor gating impairments - Cheng Xue; Xiao-Hui Li; Hong-Qun Ding; Xin Qian; Meng-Yu Zhang; Kai Chen; Zi-Wei Wei; Ying Li; Jun-Hai Jia; Wei-Ning Zhang (Metabolic Brain Disease, 2024)

Whole-genome mutagenesis of whiteleg shrimp (Litopenaeus vannamei) by ARTP and analysis of its mutational characteristics - Qiang Fu; Jingxin Zhou; Sheng Luan; Kun Luo; Baolong Chen; Jiawang Cao; Xupeng Li; Qun Xing; Jie Kong; Xianhong Meng (Aquaculture, 2024)

Co-existence of airborne SARS-CoV-2 infection and non-infection in three connected zones of a restaurant - Wei Jia; Qun Wang; David Christopher Lung; Pak-To Chan; Peihua Wang; Edwin Chung-Hin Dung; Tiffany Didik; Garnet Kwan-Yue Choi; Herman Tse; Yijie Wu; Te Miao; Wenzhao Chen; et al. (Journal of Hazardous Materials, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

Interaction of diesel exhaust particulate matter with mucins in simulated saliva fluids: Bioaccessibility of heavy metals and potential health risks - Jiao Li; Haorang Song; Linfeng Zhang; Jie Li; Yanlin Yang; Xiangfen Cui; Anjum Mahfuza; Yan Cao; Xuewei Hu; Chen Li; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2024)

Transcriptional regulation and functional validation analysis of the McbZIP1 in Mentha canadensis L. - Xu Yu; Shumin Li; Taolan Xiao; Xiwu Qi; Hailing Fang; Li Li; Yang Bai; Dongmei Liu; Qun Liu; Zequn Chen; Zhichao Xue; Chengyuan Liang (Plant Science, 2024)

Compound probiotics starter: A solution for aflatoxin B1 reduction and meat quality improvement in fermented chicken jerky - Hongwei Guo; Jingyan Chen; Hongli Qiu; Wenli Yang; Genfeng Li; Xinjun Ma; Junhe Liu; Qingqiang Yin; Qun Zhu (Food Control, 2024)

Synergistic ultra-high adsorption and oxidation of arsenic in groundwater by iron-modified biochar: Mechanisms and potential application - Jing Wei; Lina Wang; Yihan Liu; Da Ding; Qun Li; Yousheng Liu; Yun Chen; Meng Mao; Shaopo Deng (Chemical Engineering Journal, 2024)

MXene-supported Co3Ti and single-atom Co catalyst activated PMS for efficient removal of Pb-EDTA: The involvement of Co (Ⅳ) - Haoran Song; Longyu Chen; Yi hang Xu; Chen Li; Xuewei Hu; Yingjie Li; Shugen Liu; Jianhong Huang; Qun Zhao; Jie Li; Senlin Tian (Chemical Engineering Journal, 2024)

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Trifolium repens L. recruits root-associated Microbacterium species to adapt to heavy metal stress in an abandoned Pb-Zn mining area - Xin-qi Yuan; Yi-yi Liu; Si-chen Wang; Ya-qi Lu; Yin-jie Li; Jin-quan Chen; Chang-qun Duan (Science of The Total Environment, 2024)

Lappanolides A−N, fourteen undescribed sesquiterpenoids from Saussurea costus (Syn. Saussurea lappa) and their anti HBV activity - Hong-Bo Li; Shi-Qun Bai; Teng-Yun Shu; Qiong Wang; Hao Chen; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Study on the microbial mechanisms of enhancing Agaricus bisporus growth through inoculation with Pseudomonas putida - Hongtu Li; Lanhua Liu; Boyang Xu; Xiaoming Yan; Qun Chen; Xiaolei Wu; Xunfeng Wu; Dongdong Mu; Xingjiang Li (Food Bioscience, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Programmable bionanocomposite coated fertilizers for prolonged controlled release of nitrogen - Jiaxuan Liu; Yue Yuan; Ji Gao; Zhaoxian Qin; Wenbo Peng; Akanksha Lakra; Yuxuan Zhang; Shugang Zhang; Guodong Liu; Yongsheng Chen; Qun Li; Zhaohui Tong (Chemical Engineering Journal, 2024)

Fabrication of passive cooling fabric as thermal management curtain for building energy-saving - Chao-Qun Ma; Chao-Hua Xue; Xiao-Jing Guo; Wenzhao Shi; Hui-Di Wang; Meng-Chen Huang; Li Wan; Yong-Gang Wu; Jun Cheng (Chemical Engineering Journal, 2024)

Erratum to: A justice and innovative way ahead of consumption-based emission accounting approach - Qun Shen; Hongbo Duan; Yun Tang; Linbing Tang; Li Shang; Xinyu Dou; Wei Wei; Weiqiang Chen; Zhu Liu (Science China Earth Sciences, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Liquidambaric acid inhibits the proliferation of hepatocellular carcinoma cells by targeting PPARα-RXRα to down-regulate fatty acid metabolism - Xinyun Zhao; Xinping Zhu; Honglei Tao; Hongling Zou; Jili Cao; Yuxin Chen; Ziru Zhang; Yongqiang Zhu; Qun Li; Mingqian Li (Toxicology and Applied Pharmacology, 2024)

An investigation of a self-powered low-frequency nonlinear vibration isolation system - Ze-Qi Lu; Rong-Biao Hao; Dao Wu; Hu Ding; Li-Qun Chen (Engineering Structures, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Molybdenum isotopic evidence for the initiation of a big mantle wedge beneath eastern Asia - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Qi Chen; Jun Yan; Dayu Zhang; Ding-Sheng Jiang (Chemical Geology, 2024)

Three new α -pyrone derivatives from the soil-derived fungus Penicillium herquei MA-370 - Sui-Qun Yang; Xiao-Ming Li; Xiao-Dan Chen; Xin Li; Bin-Gui Wang (Natural Product Research, 2024)

A justice and innovative way ahead of consumption-based emission accounting approach - Qun Shen; Hongbo Duan; Yun Tang; Linbing Tang; Li Shang; Xinyu Dou; Wei Wei; Weiqiang Chen; Zhu Liu (Science China Earth Sciences, 2024)

The microbial electrolysis cell combined with anaerobic digestion for high salinity landfill leachate treatment: Operation parameter optimization, microbial analysis and degradation pathways - Jiachen Zhu; Qun Zhang; Mengmeng Li; Faqian Sun; He Liu; Minhua Cui; Chongjun Chen (Journal of Water Process Engineering, 2024)

Utilization of the waste aqueous phase from tea residue hydrothermal carbonization for preparing active food packaging films - Wenhui Zheng; Danmin Yang; Xu Zeng; Qun Liu; Chunchun Wang; Xialing Wu; Meng Li; Yue Liu; Linjing Chen; Wuyin Weng; Yucang Zhang (Food Chemistry, 2024)

A state-of-the-art review on the dynamic design of nonlinear energy sinks - Xiao-Feng Geng; Hu Ding; Jin-Chen Ji; Ke-Xiang Wei; Xing-Jian Jing; Li-Qun Chen (Engineering Structures, 2024)

Urbanization impact on meteorological condition and O3 concentration under past and future climates scenarios over the Greater Bay Area in Southern China - Qun Wang; Yiang Chen; Xingcheng Lu; Guangzhao Chen; Zhenning Li; Meng Cai; Chao Ren; Jimmy C.H. Fung (Atmospheric Environment, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Parametric resonance of pipe conveying pulsating fluid with initial geometric imperfection - Meng-Yuan Hao; Hu Ding; Xiao-Ye Mao; Sha Wei; Li-Qun Chen (Ocean Engineering, 2024)

Mo-Mg isotopes trace the role of serpentinite in generating arc magmatism - Qing-Chen Yang; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Guo-Chao Sun; Bing Gong (Chemical Geology, 2024)

Identification of candidate genes for Fusarium head blight resistance from QTLs using RIL population in wheat - Mingxia Zhang; Peng Jiang; Qun Wu; Xu Han; Junxia Man; Junsheng Sun; Jinlong Liang; Jingchuan Chen; Qi Zhao; Ying Guo; Yanrong An; Haiyan Jia; et al. (Plant Molecular Biology, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

The implications of lipid mobility, drug-enhancers (surfactants)-skin interaction, and TRPV1 activation on licorice flavonoid permeability - Zhuxian Wang; Hongkai Chen; Tao Liang; Yi Hu; Yaqi Xue; Yufan Wu; Quanfu Zeng; Yixin Zheng; Yinglin Guo; Zeying Zheng; Dan Zhai; Peiyi Liang; et al. (Drug Delivery and Translational Research, 2024)

A Novel Bacillus amyloliquefaciens Specifically Improving the Solubility and Antioxidant Activities of Edible Bird’s Nest - Xin-Lin Li; Jian-Mei Lian; Xiao-Ling Chen; Qun-Yan Fan; Ying Yan; Feng-Jie Cui (Current Microbiology, 2024)

Efficient turn-on fluorescent probe cooperated by cascade response for disclosing the fluctuation of cysteine in cells - Li Meng; Zi Yi Xu; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Analytica Chimica Acta, 2024)

Construction and application of a novel WGAN-CNN-based predicting approach for dust concentration at underground coal mine working faces - Banghao Zhou; Botao Qin; Qun Zhou; Daowei Sun; Pengpeng Chen; Kai Yang; Qingyan Pan; Huizhen Li (Environmental Science and Pollution Research, 2024)

Improved bacterial composition and co-occurrence patterns of rhizosphere increased nutrient uptake and grain yield through cultivars mixtures in maize - Xucun Jia; Haipeng Shang; Yibo Chen; Mengjie Lin; Yuepeng Wei; Yuxia Li; Rongfa Li; Pengfei Dong; Yinglong Chen; Yongen Zhang; Qun Wang (Science of The Total Environment, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

A novel derivative synchronous fluorescence method for the rapid, non-destructive and intuitive differentiation of denitrifying bacteria - Huang-Zhou Lv; Jinliang Chen; Yan Zhao; Yu Li; Shuo-Hui Cao; Wei-Peng Cai; Liang Shen; Yinghua Lu; Yao-Qun Li (Journal of Environmental Management, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Multifunctional Eu3+-MOF for simultaneous quantification of malachite green and leuco-malachite green and efficient adsorption of malachite green - Yi-Fan Xia; Hou-Qun Yuan; Chen Qiao; Wei Li; Ran Wang; Peiyao Chen; Yan-Xia Li; Guang-Ming Bao (Journal of Hazardous Materials, 2024)

Interactions between inhalable aged microplastics and lung surfactant: Potential pulmonary health risks - Yan Cao; Qun Zhao; Fanshu Jiang; Yingxue Geng; Haoran Song; Linfeng Zhang; Chen Li; Jie Li; Yingjie Li; Xuewei Hu; Jianhong Huang; Senlin Tian (Environmental Research, 2024)

Forced resonance of a buckled beam flexibly restrained at the inner point - Jie Jing; Zhi-Hua Shao; Xiao-Ye Mao; Hu Ding; Li-Qun Chen (Engineering Structures, 2024)

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

The decomposition of algae has a greater impact on heavy metal transformation in freshwater lake sediments than that of macrophytes - Si-Min Xue; Shu-Qi Jiang; Rui-Ze Li; Yi-Ying Jiao; Qun Kang; Li-Ya Zhao; Zhao-hua Li; Mo Chen (Science of The Total Environment, 2024)

Emergence and mobilization of a novel lincosamide resistance gene lnu(I): From environmental reservoirs to pathogenic bacteria - Zhishuang Yang; Tianjing Lan; Hongyan Luo; Pei Li; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Science of The Total Environment, 2024)

Mechanically stable superhydrophobic coating of crosslinked polymer composite with self-healing ability - Xiao-Jing Guo; Meng-Chen Huang; Chao-Hua Xue; Hui-Di Wang; Zhong-Xue Bai; Yong-Gang Wu; Chao-Qun Ma; Zhong-Yang Shao; Zi-Hao Jiang; Li Wan; A-Jun Chang; Jing Li; et al. (Chemical Engineering Journal, 2024)

Hypoxia-triggered tumor specific glutamine inhibition for reversing cisplatin resistance of chemotherapy - Jiaying Zhang; Jinghui Hu; Weiwei Zhu; Yurong Liu; Song Li; Haoting Chen; Fangling Liao; Qun Zhang; Xuan Sun; Xinting Li; Yafang Xiao; Jing Chen (Chemical Engineering Journal, 2024)

Spatial nonuniformity of landslide dam deposition and its quantitative characterization - Xing Li; Qun Chen; Zhaozhao Liu; Chen Chen (Natural Hazards, 2024)

Persulfate-based remediation of organic-contaminated soil: Insight into the impacts of natural iron ions and humic acids with complexation/redox functionality - Zhenzhen Wang; Xiaolei Jia; Wei Sun; Jianfei Wang; Chen Li; Qun Zhao; Yingjie Li; Senlin Tian (Science of The Total Environment, 2023)

Interactions between CuO NPs and PS: The release of copper ions and oxidative damage - Yan Cao; Senlin Tian; Yingxue Geng; Linfeng Zhang; Qun Zhao; Jie Chen; Yingjie Li; Xuewei Hu; Jianhong Huang; Ping Ning (Science of The Total Environment, 2023)

Multiomics reveals the formation pathway of volatile compounds in preserved egg yolk (PEY) induced by NaCl: Based on the model of PEY and salted egg yolk (SEY) treated with/without NaCl - Xiaole Xiang; Le Chen; Shiqin Dong; Faxiang Wang; Xianghong Li; Yiqun Huang; Yongle Liu; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2023)

Effect of land surface parameters on meteorology and ozone air quality simulations in the Great Bay Area, China - Qun Wang; Yiang Chen; Tung Fung; Zhenning Li; Yeqi Huang; Michael Mau Fung Wong; Xingcheng Lu (Atmospheric Environment, 2023)

Enhancing degradation of organic matter in microbial electrolytic cells coupled with anaerobic digestion (MEC-AD) systems by carbon-based materials - Mengmeng Li; Qun Zhang; Yang Liu; Jiachen Zhu; Faqian Sun; Min-Hua Cui; He Liu; Tian C. Zhang; Chongjun Chen (Science of The Total Environment, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

High efficient alkaline hydrogen evolution catalyzed by W2COx-Ru composite system containing bridged oxygen - Yu Dai; Hong Chuan Fu; Xiao Hui Chen; Qing Zhang; Ting Li; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Investigation of Campbell mode with automatic calibration operated in fission chamber-based neutron flux monitoring system on EAST - Li Yang; Li-Qun Hu; Guo-Qiang Zhong; Hong-Rui Cao; Jin-Long Zhao; Yong-Qiang Zhang; Wei-Kun Chen (Annals of Nuclear Energy, 2023)

HVT-vectored H7 vaccine protects chickens from lethal infection with the highly pathogenic H7N9 Avian inﬂuenza virus - Yi-qun Chen; Guan-ming Su; Jia-hao Zhang; Bo Li; Kai-xiong Ma; Xu Zhang; Li-hong Huang; Ming Liao; Wen-bao Qi (Veterinary Microbiology, 2023)

The effect of microbial electrolysis cell coupled with anaerobic digestion for landfill leachate treatment - Mengmeng Li; Qun Zhang; Faqian Sun; Min-Hua Cui; He Liu; Chongjun Chen (Journal of Water Process Engineering, 2023)

A preliminary study of landslide dam failures induced by the combined influence of piping and overtopping - Chen Chen; Yanlong Wang; Jianmin Zhang; Han Zhang; Huanyun Li; Qun Chen (Journal of Hydrology, 2023)

Red mud with enhanced dealkalization performance by supercritical water technology for efficient SO2 capture - Zimeng Nie; Qun Zhao; Qilin Zhao; Yingjie Li; Dian Yang; Huaying Liu; Shupu Yang; Jie Li; Senlin Tian; Chen Li; Cheng Tie; Jianhong Huang; et al. (Journal of Environmental Management, 2023)

‘Sandwich treatment’ for posterior fossa brain metastases with volume larger than 4cm3: a multicentric retrospective study - Zheng Wang; Haining Chen; Qun Chen; Yucun Zhu; Min Li; Zhou Jia (Clinical & Experimental Metastasis, 2023)

Spatiotemporal transmission of infectious particles in environment: A case study of Covid-19 - Hamed Karimian; Qin Fan; Qun Li; Youliang Chen; Juan Shi (Chemosphere, 2023)

Study on the removal and degradation mechanism of microcystin-LR by the UV/Fenton system - Zhuang Li; Jiling Chen; Canmei Wang; Jinjin Zhao; Qun Wei; Xiangmeng Ma; Gairen Yang (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Ridge tillage increased halophyte fine root production and turnover rates by altering soil properties in an abandoned farmland in northwest China - Xu Zheng; Chao-qun Chen; Lu-hua Li; Jia-ping Wang (Rhizosphere, 2023)

Co-pyrolysis characteristics of forestry and agricultural residues and waste plastics: Thermal decomposition and products distribution - Shuaihua Guo; Zhiwei Wang; Gaofeng Chen; Mengju Zhang; Tanglei Sun; Qun Wang; Zhimin Du; Yan Chen; Mengge Wu; Zaifeng Li; Tingzhou Lei; Kiran R.G. Burra; et al. (Process Safety and Environmental Protection, 2023)

Uncovering the virome and its interaction with antibiotic resistome during compost fertilization - Qingxia Zhang; Lei Zhou; Yilong Zhao; Shuhong Gao; Yanjun Yang; Qingyun Chen; Wenhui Li; Qi Qi; Qiang Dong; Jiesi Lei; Xue Guo; Qun Gao; et al. (Journal of Hazardous Materials, 2023)

Radiation and energetics of M2 internal tides in the Okhotsk Sea - Qun Li; Shuya Wang; Xu Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Antibacterial polyketides and ascochlorins from deep-sea cold-seep-derived fungus Furcasterigmium furcatum (syn. Acremonium furcatum) - Xiao-Dan Chen; Sui-Qun Yang; Xiao-Ming Li; Bin-Gui Wang; Xin Li (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

A new xanthene-based platform for developing NIR fluorogenic probes for in vivo bioimaging - Xiao-Fan Zhang; Lin Shen; Sheng Wang; Qian Chen; Xiao-Qun Cao; Shi-Li Shen; Xiaohua Li (Chemical Engineering Journal, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Correction: Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

Static bifurcation and nonlinear vibration of pipes conveying fluid in thermal environment - Xiao-Ye Mao; Si-Yu Gao; Hu Ding; Li-Qun Chen (Ocean Engineering, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Deleting UL49.5 in duck plague virus causes attachment, entry and spread defects - Chunmei Li; Mingshu Wang; Anchun Cheng; Bin Tian; Juan Huang; Ying Wu; Qiao Yang; Qun Gao; Di Sun; Shaqiu Zhang; Xumin Ou; Sai Mao; et al. (Veterinary Microbiology, 2023)

Occam’s Razor-Inspired Nb2C delivery platform potentiates breast cancer therapy and inhibits lung metastasis - Xiangping Lin; Zhongjun Li; Shuang Du; Qun Wang; Yucheng Guan; Guopan Cheng; Huijie Hong; Jianqing Li; Xiaojia Chen; Tongkai Chen (Chemical Engineering Journal, 2023)

Single-cell-resolution transcriptome map revealed novel genes involved in testicular germ cell progression and somatic cells specification in Chinese tongue sole with sex reversal - Hong-Yan Wang; Xiang Liu; Jian-Yang Chen; Yingyi Huang; Yifang Lu; Fujian Tan; Qun Liu; Mingming Yang; Shuo Li; Xianghui Zhang; Yating Qin; Wenxiu Ma; et al. (Science China Life Sciences, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

On the Generation and Evolution of Internal Solitary Waves in the Andaman Sea - Yujun Yu; Tao Xu; Jinhu Wang; Shuya Wang; Qun Li; Jing Meng; Xu Chen; Kexiao Lu; Guixia Wang (Journal of Ocean University of China, 2023)

Elevated ozone enhances the network stability of rhizospheric bacteria rather than fungi - Zhengsheng Yu; Xin Chen; Feng Hua Zhai; Qun Gao; Xun Wen Chen; Xue Guo; Yansen Xu; Meng Ying Gao; Cehui Mo; Zhaozhong Feng; Yunfeng Yang; Hui Li (Agriculture, Ecosystems & Environment, 2023)

A deep unrolling pansharpening method based on spectral consistency and double spatial priors - Dajiang Lei; Xin Luo; Hao Chen; Liping Zhang; Qun Liu; Weisheng Li (International Journal of Remote Sensing, 2023)

Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2023)

Cascading effects of Pb on the environmental and symbiotic microbiota and tadpoles' physiology based on field data and laboratory validation - Wei Zhu; Yan Lv; Qun-De Zhang; Li-Ming Chang; Qi-Heng Chen; Bin Wang; Jian-Ping Jiang (Science of The Total Environment, 2023)

Deep learning drives efficient discovery of novel antihypertensive peptides from soybean protein isolate - Yiyun Zhang; Zijian Dai; Xinjie Zhao; Changyu Chen; Siqi Li; Yantong Meng; Zhuoma Suonan; Yuge Sun; Qun Shen; Liyang Wang; Yong Xue (Food Chemistry, 2023)

Identification and characterization of two long-type peptidoglycan recognition proteins, PGRP-L1 and PGRP-L2, in the orange-spotted grouper, Epinephelus coioides - Jing Hou; Wei Hao; Min Chang Li; Zhen Gan; Shan Nan Chen; Yi Shan Lu; Li Qun Xia (Fish & Shellfish Immunology, 2023)

Is the sacrificial agent really just a sacrificial agent? A case study on the photocatalytic reduction of U(VI) by alcohols - Si-Yu Chen; Ji-Pan Yu; Zhi-Fang Chai; Wei-Qun Shi; Li-Yong Yuan (Chemical Engineering Journal, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

Sustainable nitrogen management strategies based on nitrogen flow in urban human system - Chuanhe Xiong; Zheng Guo; Sophia Shuang Chen; Qun Gao; Ismael Aaron Kimirei; Hengpeng Li; Weizhong Su (Environmental Science and Pollution Research, 2023)

Dual seasonal pattern for hemorrhagic fever with renal syndrome and its potential determinants in China - Chen-Long Lv; Yao Tian; Yan Qiu; Qiang Xu; Jin-Jin Chen; Bao-Gui Jiang; Zhong-Jie Li; Li-Ping Wang; Simon I. Hay; Wei Liu; Li-Qun Fang (Science of The Total Environment, 2023)

Uptake kinetics and subcellular distribution of three classes of typical pesticides in rice plants - Jianan Liu; Jinjin Cheng; Chunli Zhou; Liya Ma; Xiaolong Chen; Yong Li; Xing Sun; Xiaolong Yan; Renhua Geng; Qun Wan; Xiangyang Yu (Science of The Total Environment, 2023)

Complete genome sequence of marine Roseobacter lineage member Ruegeria sp. YS9 with five plasmids isolated from red algae - Qun-Jian Yin; Fang-Chao Zhu; Hong-Zhi Tang; Xu-Yang Chen; Xin Liu; Li-Chang Tang; Xue-Gong Li (Marine Genomics, 2023)

Observed internal tides in the deep northwestern Pacific by Argo floats - Yang Wang; Zhenhua Xu; Qun Li; Zhaohui Chen; Jia You; Baoshu Yin; Robin Robertson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

An intrinsically non-flammable organic electrolyte for wide temperature range supercapacitors - Shaohui Li; Qingyong Tian; Jingwei Chen; Yining Chen; Pengzhi Guo; Cong Wei; Peng Cui; Jingyun Jiang; Xiaomeng Li; Qun Xu (Chemical Engineering Journal, 2023)

Apelin/APJ system: an emerging therapeutic target for neurological diseases - Ao Li; Qun Zhao; Linxi Chen; Zhiyue Li (Molecular Biology Reports, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Reactive nitrogen budgets in human-nature coupling system in lakeside area with insufficient data - A case study of Mwanza, Tanzania - Chuanhe Xiong; Liting Xu; Fenant Laurent Mhagama; Sophia Shuang Chen; Kexin Zhu; Qun Gao; Hengpeng Li; Weizhong Su (Science of The Total Environment, 2023)

Association of long-term air pollution exposure with the risk of prediabetes and diabetes: Systematic perspective from inflammatory mechanisms, glucose homeostasis pathway to preventive strategies - Yayuan Mei; Ang Li; Jiaxin Zhao; Quan Zhou; Meiduo Zhao; Jing Xu; Runkui Li; Yanbing Li; Kai Li; Xiaoyu Ge; Chen Guo; Yongjie Wei; et al. (Environmental Research, 2023)

Evolving a high-performance bio-imaging tool derived from a compact fluorophore as well as creating a reaction-based fluorescent probe for precise determination of Ag+ - Zi Yi Xu; Xiao Hu Wang; Sha Li Huang; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2023)

Selective catalysis of single V atoms and VN1-x nanodots enables fast polysulfides conversion in lithium–sulfur batteries - Youquan Zhang; Cheng Ma; Chunxiao Zhang; Li Ma; Shuai Zhang; Qun Huang; Chaoping Liang; Libao Chen; Liangjun Zhou; Weifeng Wei (Chemical Engineering Journal, 2023)

A review of the research on the failure potential of landslide dams caused by overtopping and seepage - Zhaozhao Liu; Qun Chen; Xing Li; Chen Chen; Cheng Zhou; Chen Wang (Natural Hazards, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

A stable method for Agrobacterium-mediated transformation of Mentha piperita and Mentha canadensis using internodal explants - Xu Yu; Zequn Chen; Shumin Li; Xiwu Qi; Hailing Fang; Yang Bai; Li Li; Dongmei Liu; Qun Liu; Weilin Li; Chengyuan Liang (In Vitro Cellular & Developmental Biology - Plant, 2022)

The heterogeneous orogenic lithospheric mantle: whole rock and mineral geochemical evidence from early Paleozoic mafic intrusives in the Qilian orogen, China - Qi Chen; Li-Qun Dai; Zi-Fu Zhao; Yong-Fei Zheng; Yao Zhou (Contributions to Mineralogy and Petrology, 2022)

Microbial succession and its effect on key aroma components during light-aroma-type Xiaoqu Baijiu brewing process - Bin Lin; Jie Tang; Qiang Yang; Zhixin Su; Liping Zhu; Qun Li; Wei Jiang; Long Zhang; Yuancai Liu; Shenxi Chen (World Journal of Microbiology and Biotechnology, 2022)

Facial emotion perception abilities are related to grey matter volume in the culmen of cerebellum anterior lobe in drug-naïve patients with first-episode schizophrenia - Xiaoxin Zhao; Jingjing Yao; Yiding Lv; Xinyue Zhang; Chongyang Han; Lijun Chen; Fangfang Ren; Qun Zhou; Zhuma Jin; Yuan Li; Yasong Du; Yuxiu Sui (Brain Imaging and Behavior, 2022)

Awareness for Endoscopic Screening Among Accompanying Children of Hospitalized Esophageal Cancer Patients in Henan - Lian Qun Zhang; Xian Juan Du; Fu You Zhou; Pei Nan Chen; Hai Ling Wang; Li Sun; Xiu Ling Li (Journal of Cancer Education, 2022)

Alterations to cognitive abilities and functional networks in rats post broad-band intense noise exposure - Xiao-Min Xu; Yu-Qun Zhang; Feng-Chao Zang; Chun-Qiang Lu; Li-Jie Liu; Jian Wang; Richard Salvi; Yu-Chen Chen; Gao-Jun Teng (Brain Imaging and Behavior, 2022)

White matter alterations in heart-kidney imbalance insomnia and Jiao-Tai-Wan treatment: A diffusion-tensor imaging study - Jie Chen; Yanxuan Li; Nengzhi Xia; Caiyun Wen; Tianyi Xia; Yuandi Zhuang; Mengmeng Jiang; Yilan Xiang; Mingyue Zhang; Chenyi Zhan; Yunjun Yang; Zhengzhong Yuan; et al. (Brain Imaging and Behavior, 2022)
Previous studies have reported changes in white matter microstructures in patients with insomnia. However, few neuroimaging studies have focused specifically on white matter tracts in insomnia patients after having received treatment. In this prospective study, diffusion-tensor imaging was used in two samples of heart-kidney imbalance insomnia patients who were treated with placebo or Jiao-Tai-Wan, a traditional Chinese medicine commonly used to treat heart-kidney imbalance insomnia, to assess the changes in white matter tracts. Tract-based spatial statistical analyses were first applied to compare the changes in mean diffusivity and fractional anisotropy of white matter between 75 heart-kidney imbalance insomnia patients and 41 healthy control participants. In subsequent randomized, double-blind, placebo-controlled trials, comparisons of mean diffusivity and fractional anisotropy were also performed in 24 heart-kidney imbalance insomnia patients (8 males; 16 females; 42.5 ± 10.4 years) with Jiao-Tai-Wan and 26 heart-kidney imbalance insomnia patients (11 males; 15 females; 39.7 ± 9.4 years) with a placebo, with age and sex as covariates. Fractional anisotropy values in left corticospinal tract were increased in heart-kidney imbalance insomnia patients. Heart-kidney imbalance insomnia patients showed lower mean diffusivity and fractional anisotropy values of several white matter tracts than healthy control participants, such as the bilateral anterior limb of internal capsule, bilateral superior longitudinal fasciculus and bilateral posterior corona radiata. After being treated with Jiao-Tai-Wan, heart-kidney imbalance insomnia patients showed a trend towards reduced fractional anisotropy values in the left corticospinal tract. Jiao-Tai-Wan may improve the sleep quality by reversing the structural changes of the left corticospinal tract caused by heart-kidney imbalance insomnia.

Comparative transcriptome analysis revealed candidate genes involved in fruiting body development and sporulation in Ganoderma lucidum - Dongmei Liu; Xueyan Sun; Wentong Diao; Xiwu Qi; Yang Bai; Xu Yu; Li Li; Hailing Fang; Zequn Chen; Qun Liu; Chengyuan Liang (Archives of Microbiology, 2022)

Identification and analysis of oil candidate genes reveals the molecular basis of cottonseed oil accumulation in Gossypium hirsutum L. - Zhibin Zhang; Juwu Gong; Zhen Zhang; Wankui Gong; Junwen Li; Yuzhen Shi; Aiying Liu; Qun Ge; Jingtao Pan; Senmiao Fan; Xiaoying Deng; Shaoqi Li; et al. (Theoretical and Applied Genetics, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Experimental and Model Predictive Investigation into the Relationship of pH Alternation with Addition of Lime in Acid Tin Tailing Treatments - Feng Yin; Ying-Jie Li; Qun Zhao; Chen Li; Jie Li; Sen-Lin Tian (Bulletin of Environmental Contamination and Toxicology, 2021)

Formation Process of Silicate-Iron Oxyhydroxide Complex and Its Influence on the Distribution of Heavy Metals in Mining Area - Qun Zhao; Jiangtao He; Xinrui Yan; Chen Li; Jie Li; YingJie Li; Senlin Tian; Jianhong Huang; Ping Ning (Bulletin of Environmental Contamination and Toxicology, 2021)

Effects of temperature on the growth and carbohydrate production of three benthic dinoflagellate species from Hainan Island, South China Sea - Zhen Wu; Hua Zhang; Qun Li; Lei Cui; Heng Chen; Songhui Lu (Ecotoxicology, 2021)

miR-378d is Involved in the Regulation of Apoptosis and Autophagy of and E2 Secretion from Cultured Ovarian Granular Cells Treated by Sodium Fluoride - Qun Chen; Zhen Li; Zhao Xu; Chen Chen; Jiawei Wang; Jinyuan Zhu; Zhaoheng Dong (Biological Trace Element Research, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Functional analysis of indole 3-hexanoic acid as a novel auxin from Arabidopsis thaliana - Ping Song; Hui Xu; Jixiu Zhang; Huatao Chen; Li Li; Yana Qu; Feng Lin; Qun Zhang (Planta, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

LncRNA FTX Promotes Colorectal Cancer Cells Migration and Invasion by miRNA-590-5p/RBPJ Axis - Guo-Qun Chen; Zhi-Ming Liao; Jiao Liu; Fang Li; Da Huang; Ya-Dong Zhou (Biochemical Genetics, 2021)

The Arabidopsis KH-domain protein FLOWERING LOCUS Y delays flowering by upregulating FLOWERING LOCUS C family members - Guang-Yi Dai; Ding-Kang Chen; Yun-Peng Sun; Wei-Yi Liang; Yu Liu; Li-Qun Huang; Yong-Kang Li; Jia-Fan He; Nan Yao (Plant Cell Reports, 2020)

Identification of immune-related gene signature predicting survival in the tumor microenvironment of lung adenocarcinoma - Mengnan Zhao; Ming Li; Zhencong Chen; Yunyi Bian; Yuansheng Zheng; Zhengyang Hu; Jiaqi Liang; Yiwei Huang; Jiacheng Yin; Cheng Zhan; Mingxiang Feng; Qun Wang (Immunogenetics, 2020)

Phosphodiesterase 2 inhibitor Hcyb1 reverses corticosterone-induced neurotoxicity and depression-like behavior - Meng-Jia Zhu; Jing Shi; Yong Chen; Guobing Huang; Xiong-Wei Zhu; Sam Zhang; Xian-Feng Huang; Guo-Qiang Song; Han-Ting Zhang; Heng-Ming Ke; James M. O’Donnell; Li-Qun Wang; et al. (Psychopharmacology, 2020)

Formulation and Characterization of a 3D-Printed Cryptotanshinone-Loaded Niosomal Hydrogel for Topical Therapy of Acne - Zhuxian Wang; Li Liu; Shijian Xiang; Cuiping Jiang; Wenfeng Wu; Shifa Ruan; Qunqun Du; Tingting Chen; Yaqi Xue; Huoji Chen; Lidong Weng; Hongxia Zhu; et al. (AAPS PharmSciTech, 2020)

Evolution of internal solitary waves on the slope-shelf topography in the northern South China Sea - Shuya Wang; Jing Meng; Qun Li; Xu Chen (Ocean Dynamics, 2020)

Whole-Brain Monosynaptic Inputs to Hypoglossal Motor Neurons in Mice - Han Guo; Xiang-Shan Yuan; Ji-Chuan Zhou; Hui Chen; Shan-Qun Li; Wei-Min Qu; Zhi-Li Huang (Neuroscience Bulletin, 2020)
Hypoglossal motor neurons (HMNs) innervate tongue muscles and play key roles in a variety of physiological functions, including swallowing, mastication, suckling, vocalization, and respiration. Dysfunction of HMNs is associated with several diseases, such as obstructive sleep apnea (OSA) and sudden infant death syndrome. OSA is a serious breathing disorder associated with the activity of HMNs during different sleep–wake states. Identifying the neural mechanisms by which the state-dependent activities of HMNs are controlled may be helpful in providing a theoretical basis for effective therapy for OSA. However, the presynaptic partners governing the activity of HMNs remain to be elucidated. In the present study, we used a cell-type-specific retrograde tracing system based on a modified rabies virus along with a Cre/loxP gene-expression strategy to map the whole-brain monosynaptic inputs to HMNs in mice. We identified 53 nuclei targeting HMNs from six brain regions: the amygdala, hypothalamus, midbrain, pons, medulla, and cerebellum. We discovered that GABAergic neurons in the central amygdaloid nucleus, as well as calretinin neurons in the parasubthalamic nucleus, sent monosynaptic projections to HMNs. In addition, HMNs received direct inputs from several regions associated with respiration, such as the pre-Botzinger complex, parabrachial nucleus, nucleus of the solitary tract, and hypothalamus. Some regions engaged in sleep–wake regulation (the parafacial zone, parabrachial nucleus, ventral medulla, sublaterodorsal tegmental nucleus, dorsal raphe nucleus, periaqueductal gray, and hypothalamus) also provided primary inputs to HMNs. These results contribute to further elucidating the neural circuits underlying disorders caused by the dysfunction of HMNs.

Illumina MiSeq sequencing and network analysis the distribution and co-occurrence of bacterioplankton in Danjiangkou Reservoir, China - Zhao-Jin Chen; Ge Xu; Chuan-Yu Ding; Bao-Hai Zheng; Yan Chen; Hui Han; Yu-Ying Li; Jian-Wei Shi; Lan-Qun Hu (Archives of Microbiology, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

In situ meta‐omic insights into the community compositions and ecological roles of hadal microbes in the Mariana Trench - Zhao‐Ming Gao; Jiao‐Mei Huang; Guo‐Jie Cui; Wen‐Li Li; Jun Li; Zhan‐Fei Wei; Jun Chen; Yong‐Zhi Xin; Du‐Si Cai; Ai‐Qun Zhang; Yong Wang (Environmental Microbiology, 2019)
Summary The low temperature and elevated hydrostatic pressure in hadal trenches at water depths below 6000 m render sample collection difficult. Here, in situ hadal water microbial samples were collected from the Mariana Trench and analysed. The hadal microbial communities at different depths were revealed to be consistent and were dominated by heterotrophic Marinimicrobia. Thirty high‐quality metagenome‐assembled genomes (MAGs) were retrieved to represent the major hadal microbes affiliated with 12 prokaryotic phyla. Most of the MAGs were newly reported and probably derived from novel hadal inhabitants as exemplified by a potentially new candidate archaeal phylum in the DPANN superphylum. Metabolic reconstruction indicated that a great number of the MAGs participated in nitrogen and sulfur cycling, in which the nitrification process was driven sequentially by Thaumarchaeota and Nitrospirae and sulfur oxidization by Rhodospirillales in the Alphaproteobacteria class. Moreover, several groups of hadal microbes were revealed to be potential carbon monoxide oxidizers. Metatranscriptomic result highlighted the contribution of Chloroflexi in degrading recalcitrant dissolved organic matter and Marinimicrobia in extracellular protein decomposition. The present work provides an in‐depth view on the hadal microbial communities regarding their endemism and element cycles.

X-linked hyper-IgM syndrome complicated with interstitial pneumonia and liver injury: a new mutation locus in the CD40LG gene - Tian-Jiao Wang; Li-Fang Wu; Junguo Chen; Wen Zhu; Hua Wang; Xiao-Lin Liu; Yi-Qun Teng (Immunologic Research, 2019)

Laboratory Experiments on an Internal Solitary Wave over a Triangular Barrier - Haidi Mu; Xu Chen; Qun Li (Journal of Ocean University of China, 2019)

Effect of boreal spring precipitation anomaly pattern change in the late 1990s over tropical Pacific on the atmospheric teleconnection - Yuanyuan Guo; Zhiping Wen; Ruidan Chen; Xiuzhen Li; Xiu–Qun Yang (Climate Dynamics, 2019)

Role of AGEs in the progression and regression of atherosclerotic plaques - Zhong-qun Wang; Le-le Jing; Jin-chuan Yan; Zhen Sun; Zheng-yang Bao; Chen Shao; Qi-wen Pang; Yue Geng; Li-li Zhang; Li-hua Li (Glycoconjugate Journal, 2018)

Genomics‐driven discovery of a novel self‐resistance mechanism in the echinocandin‐producing fungus Pezicula radicicola - Qun Yue; Yan Li; Li Chen; Xiaoling Zhang; Xingzhong Liu; Zhiqiang An; Gerald F Bills (Environmental Microbiology, 2018)
Summary The echinocandins are antifungal lipopeptides targeting fungi via noncompetitive inhibition of the β‐1,3‐ d ‐glucan synthase FKS1 subunit. A novel echinocandin resistance mechanism involving an auxiliary copy of FKS1 in echinocandin‐producing fungus Pezicula radicicola NRRL 12192 was discovered. We sequenced the genome of NRRL 12192 and predicted two FKS1‐encoding genes ( prfks1n and prfks1a ), rather than a single FKS1 gene typical of filamentous ascomycetes. The prfks1a gene sits immediately adjacent to an echinocandin (sporiofungin) gene cluster, which was confirmed by disruption of prnrps4 and abolishment of sporiofungin production. Disruption of prfks1a dramatically increased the strain's sensitivity to exogenous echinocandins. In the absence of echinocandins, transcription levels of prfks1a relative to β ‐tubulin in the wild type and in Δ prnrps4 stains were similar. Moreover, prfks1a is consistently transcribed at low levels and is upregulated in the presence of exogenous echinocandin, but not during growth conditions promoting endogenous production of sporiofungin. Therefore, we conclude that prfks1a is primarily responsible for protecting the fungus against extracellular echinocandin toxicity. The presence of unclustered auxiliary copies of FKS1 with high similarity to prfks1a in two other echinocandin‐producing strains suggests that this previously unrecognized resistance mechanism may be common in echinocandin‐producing fungi of the family Dermataceae of the class Leotiomycetes.

Enfumafungin synthase represents a novel lineage of fungal triterpene cyclases - Eric Kuhnert; Yan Li; Nan Lan; Qun Yue; Li Chen; Russell J. Cox; Zhiqiang An; Kenichi Yokoyama; Gerald F. Bills (Environmental Microbiology, 2018)
Summary Enfumafungin is a glycosylated fernene‐type triterpenoid produced by the fungus Hormonema carpetanum . Its potent antifungal activity, mediated by its interaction with β ‐1,3‐glucan synthase and the fungal cell wall, has led to its development into the semi‐synthetic clinical candidate, ibrexafungerp (=SCY‐078). We report on the preliminary identification of the enfumafungin biosynthetic gene cluster (BGC) based on genome sequencing, phylogenetic reconstruction, gene disruption, and cDNA sequencing studies. Enfumafungin synthase (e fuA ) consists of a terpene cyclase domain (TC) fused to a glycosyltransferase (GT) domain and thus represents a novel multifunctional enzyme. Moreover, the TC domain bears a phylogenetic relationship to bacterial squalene–hopene cyclases (SHC) and includes a typical DXDD motif within the active centre suggesting that efuA evolved from SHCs. Phylogenetic reconstruction of the GT domain indicated that this portion of the fusion gene originated from fungal sterol GTs. Eleven genes flanking efuA are putatively involved in the biosynthesis, regulation, transport and self‐resistance of enfumafungin and include an acetyltransferase, three P450 monooxygenases, a dehydrogenase, a desaturase and a reductase. A hypothetical scheme for enfumafungin assembly is proposed in which the E‐ring is oxidatively cleaved to yield the four‐ring system of enfumafungin. EfuA represents the first member of a widespread lineage of fungal SHCs.

Gut Microbiota and its Modulation for Healthy Farming of Pacific White Shrimp Litopenaeus vannamei - Erchao Li; Chang Xu; Xiaodan Wang; Shifeng Wang; Qun Zhao; Meiling Zhang; Jian G. Qin; Liqiao Chen (Reviews in Fisheries Science & Aquaculture, 2018)

Genetic analysis of the fiber quality and yield traits in G. hirsutum background using chromosome segments substitution lines (CSSLs) from Gossypium barbadense - Lixue Guo; Yuzhen Shi; Juwu Gong; Aiying Liu; Yunna Tan; Wankui Gong; Junwen Li; Tingting Chen; Haihong Shang; Qun Ge; Quanwei Lu; Jie Sun; et al. (Euphytica, 2018)

Laboratory tests and numerical simulations on the impact of subsurface barriers to saltwater intrusion - Fu-lin Li; Xue-qun Chen; Cai-hong Liu; Yan-qing Lian; Li He (Natural Hazards, 2018)

Identification of the genes in tea leafhopper, Empoasca onukii (Hemiptera: Cicadellidae), that encode odorant-binding proteins and chemosensory proteins using transcriptome analyses of insect heads - Lei Bian; Zhao-Qun Li; Long Ma; Xiao-Ming Cai; Zong-Xiu Luo; Zong-Mao Chen (Applied Entomology and Zoology, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Crowding-out effect of coal industry investment in coal mining area: taking Shanxi province in China as a case - Li Li; Yalin Lei; Qun Xu; Sanmang Wu; Dan Yan; Jiabin Chen (Environmental Science and Pollution Research, 2017)

Bamboo invasion of broadleaf forests altered soil fungal community closely linked to changes in soil organic C chemical composition and mineral N production - Yongchun Li; Yongfu Li; Scott X. Chang; Qiufang Xu; Zhiying Guo; Qun Gao; Ziyan Qin; Yunfeng Yang; Junhui Chen; Xue Liang (Plant and Soil, 2017)

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Individual and combined inhibition of phenol and thiocyanate on microbial activity of partial nitritation - Qiong Guo; Zhi-Jian Shi; Chen-Chen Yang; Mei Huang; Jia-Li Xu; Yi-Qun Xu; Wei-Min Ni; Ren-Cun Jin (Environmental Science and Pollution Research, 2017)

Ecotoxicological bioassays of sediment leachates in a river bed flanked by decommissioned pesticide plants in Nantong City, East China - Yan Zhou; Fenghe Wang; Jinzhong Wan; Jian He; Qun Li; Qiang Chen; Jay Gao; Yusuo Lin; Shengtian Zhang (Environmental Science and Pollution Research, 2017)

Low-Dose Ethanol Preconditioning Protects Against Oxygen-Glucose Deprivation/Reoxygenation-Induced Neuronal Injury By Activating Large Conductance, Ca2+-Activated K+ Channels In Vitro - Fang Su; An-Chen Guo; Wei-Wei Li; Yi-Long Zhao; Zheng-Yi Qu; Yong-Jun Wang; Qun Wang; Yu-Lan Zhu (Neuroscience Bulletin, 2017)

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation - Lv Yin; Peng Yong-bo; Yu Meng-Fei; Chen Weiwei; Zhao Ping; Xue Lu; Ma Li-Qun; Cai Congli; Liu Qing-hua; Shen Jinhua (Journal of Physiology and Biochemistry, 2017)

Continuous supply of recycled Pacific oceanic materials in the source of Cenozoic basalts in SE China: the Zhejiang case - Shao-Chen Liu; Qun-Ke Xia; Sung Hi Choi; Etienne Deloule; Pei Li; Jia Liu (Contributions to Mineralogy and Petrology, 2016)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

Genetic alterations of δ-catenin/NPRAP/Neurojungin (CTNND2): functional implications in complex human diseases - Qun Lu; Byron J. Aguilar; Mingchuan Li; Yongguang Jiang; Yan-Hua Chen (Human Genetics, 2016)

The P450 oxidoreductase (POR) rs2868177 and cytochrome P450 (CYP) 2B6*6 polymorphisms contribute to the interindividual variability in human CYP2B6 activity - Li-chen Gao; Fang-qun Liu; Li Yang; Lin Cheng; Hai-ying Dai; Ran Tao; Shi-Peng Cao; Di Wang; Jie Tang (European Journal of Clinical Pharmacology, 2016)

Glutathione improves survival of cryopreserved embryogenic calli of Agapanthus praecox subsp. orientalis - Guan-qun Chen; Li Ren; Di Zhang; Xiao-hui Shen (Acta Physiologiae Plantarum, 2016)

An epidemic of coxsackievirus B3 infection in infants and children in Jiangsu Province, China: a prospective cohort study - Fan Gao; Lian-lian Bian; Qun-ying Mao; Pan Chen; Xin Yao; Jing-xin Li; Feng-cai Zhu; Zheng-lun Liang (Archives of Virology, 2016)

Two generalized algorithms measuring phase–amplitude cross-frequency coupling in neuronal oscillations network - Qun Li; Chen-guang Zheng; Ning Cheng; Yi-yi Wang; Tao Yin; Tao Zhang (Cognitive Neurodynamics, 2016)

Genomic and physiological analysis reveals versatile metabolic capacity of deep-sea Photobacterium phosphoreum ANT-2200 - Sheng-Da Zhang; Claire-Lise Santini; Wei-Jia Zhang; Valérie Barbe; Sophie Mangenot; Charlotte Guyomar; Marc Garel; Hai-Tao Chen; Xue-Gong Li; Qun-Jian Yin; Yuan Zhao; Jean Armengaud; et al. (Extremophiles, 2016)

Comprehensive analysis of NAC transcription factors in diploid Gossypium: sequence conservation and expression analysis uncover their roles during fiber development - Haihong Shang; Zhongna Wang; Changsong Zou; Zhen Zhang; Weijie Li; Junwen Li; Yuzhen Shi; Wankui Gong; Tingting Chen; Aiying Liu; Juwu Gong; Qun Ge; et al. (Science China Life Sciences, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Transcriptomic profiling revealed the regulatory mechanism of Arabidopsis seedlings response to oxidative stress from cryopreservation - Li Ren; Di Zhang; Guan-qun Chen; Barbara M. Reed; Xiao-hui Shen; Huo-ying Chen (Plant Cell Reports, 2015)

Effect of lipopolysaccharide on the hemocyte apoptosis of Eriocheir sinensis - Hai-sheng Xu; Sun-jian Lyu; Jie-hao Xu; Bin-jie Lu; Jing Zhao; Song Li; Yi-qun Li; Yu-yin Chen (Journal of Zhejiang University-SCIENCE B, 2015)

The acute effects of outdoor temperature on blood pressure in a panel of elderly hypertensive patients - Renjie Chen; Jianxiong Lu; Qun Yu; Li Peng; Dandan Yang; Cuicui Wang; Haidong Kan (International Journal of Biometeorology, 2015)

ROS-induced oxidative stress and apoptosis-like event directly affect the cell viability of cryopreserved embryogenic callus in Agapanthus praecox - Di Zhang; Li Ren; Guan-qun Chen; Jie Zhang; Barbara M. Reed; Xiao-hui Shen (Plant Cell Reports, 2015)

Molecular survey of Tamyb10-1 genes and their association with grain colour and germinability in Chinese wheat and Aegilops tauschii - ZHONG DONG DONG; JIE CHEN; TING LI; FENG CHEN; DANG QUN CUI (Journal of Genetics, 2015)

Isolation of a new flavanone from Daidai fruit and hypolipidemic activity of total flavonoids extracts - Ling-Jun Zeng; Dan Chen; Qing-De Huang; Qun Huang; Yun-Fang Lian; Wei-Wei Cai; Hua-Ping Zeng; Yi-Li Lin (Natural Product Research, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

Reconstructing atmospheric CO 2 during the Plio–Pleistocene transition by fossil Typha - Yun‐Jun Bai; Li‐Qun Chen; Parminder S. Ranhotra; Qing Wang; Yu‐Fei Wang; Cheng‐Sen Li (Global Change Biology, 2015)
The Earth has undergone a significant climate switch from greenhouse to icehouse during the Plio–Pleistocene transition ( PPT ) around 2.7–2.4 million years ago (Ma), marked by the intensification of the Northern Hemisphere glaciation ( NHG ) ~2.7 Ma. Evidence based on oceanic CO 2 [( CO 2 ) aq ], supposed to be in close equilibrium with the atmospheric CO 2 [( CO 2 ) atm ], suggests that the CO 2 decline might drive such climate cooling. However, the rarity of direct evidence from [ CO 2 ] atm during the interval prevents determination of the atmospheric CO 2 level and further assessment on the impact of its fluctuation. Here, we reconstruct the [ CO 2 ] atm level during 2.77–2.52 Ma based on a new developed proxy of stomatal index on Typha orientalis leaves from Shanxi, North China, and depict the first [ CO 2 ] atm curve over the past 5 Ma by using stomata‐based [ CO 2 ] atm data. Comparisons of the terrestrial‐based [ CO 2 ] atm and the existed marine‐based [ CO 2 ] aq curves show a similar general trend but with different intensity of fluctuations. Our data reveal that the high peak of [ CO 2 ] atm occurred at 2.77–2.52 Ma with a lower [ CO 2 ] aq background. The subsequent sharp fall in [ CO 2 ] atm level might be responsible for the intensification of the NHG based on their general temporal synchronism. These findings shed a significant light for our understanding toward the [ CO 2 ] atm changes and its ecological impact since 5 Ma.

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

The association between C-159T polymorphism in CD14 gene and susceptibility to tuberculosis: a meta-analysis - Qing Yuan; Huifang Chen; Xueyan Zheng; Xiaming Chen; Qun Li; Yanping Zhang; Xiaorong Zhang; Tingli Shi; Junhua Zhou; Qing Chen; Shouyi Yu (Molecular Biology Reports, 2014)

Identifying and Characterizing Resting State Networks in Temporally Dynamic Functional Connectomes - Xin Zhang; Xiang Li; Changfeng Jin; Hanbo Chen; Kaiming Li; Dajiang Zhu; Xi Jiang; Tuo Zhang; Jinglei Lv; Xintao Hu; Junwei Han; Qun Zhao; et al. (Brain Topography, 2014)

Study on internal waves generated by tidal flow over critical topography - Xiaona Jia; Xu Chen; Qun Li; Qiang Li (Journal of Ocean University of China, 2014)

Catechin ameliorates cardiac dysfunction in rats with chronic heart failure by regulating the balance between Th17 and Treg cells - Qi Zhang; Li-qun Hu; Chang-sen Yin; Ping Chen; Hong-qi Li; Xin Sun; Guang Yan (Inflammation Research, 2014)

Is right ventricular mid-septal pacing superior to apical pacing in patients with high degree atrio-ventricular block and moderately depressed left ventricular function? - Kang Chen; Ye Mao; Shao-hua Liu; Qiong Wu; Qing-zhi Luo; Wen-qi Pan; Qi Jin; Ning Zhang; Tian-you Ling; Ying Chen; Gang Gu; Wei-feng Shen; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Overexpression of leucine aminopeptidase 3 contributes to malignant development of human esophageal squamous cell carcinoma - Shu Zhang; Xiaojing Yang; Hui Shi; Mei Li; Qun Xue; Hanru Ren; Li Yao; Xueyu Chen; Jianguo Zhang; Huijie Wang (Journal of Molecular Histology, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Overexpression of PTP1B in human colorectal cancer and its association with tumor progression and prognosis - Queting Chen; Yong Li; Zhong Li; Qun Zhao; Liqiao Fan (Journal of Molecular Histology, 2014)

Optimized expression in Pichia pastoris eliminates common protein contaminants from subsequent His-tag purification - Yong Chen; Yang Li; Peng Liu; Qun Sun; Zhu Liu (Biotechnology Letters, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Diffusion tensor imaging reveals evolution of primate brain architectures - Degang Zhang; Lei Guo; Dajiang Zhu; Kaiming Li; Longchuan Li; Hanbo Chen; Qun Zhao; Xiaoping Hu; Tianming Liu (Brain Structure and Function, 2013)

Quantification of Swelling and Erosion in the Controlled Release of a Poorly Water-Soluble Drug Using Synchrotron X-ray Computed Microtomography - Xianzhen Yin; Haiyan Li; Zhen Guo; Li Wu; Fangwei Chen; Marcel de Matas; Qun Shao; Tiqiao Xiao; Peter York; You He; Jiwen Zhang (The AAPS Journal, 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Development and identification of a wheat-Leymus mollis multiple alien substitution line - Ji-Xin Zhao; Wan-Li Du; Jun Wu; Xue-Ni Cheng; Yang Gao; Yu-Hui Pang; Xin-Hong Chen; Shu-Hui Liu; Qun-Hui Yang; Jie Fu (Euphytica, 2013)

Influence of igneous processes and serpentinization on geochemistry of the Logatchev Massif harzburgites (14°45′N, Mid-Atlantic Ridge), and comparison with global abyssal peridotites - Zhi-qiang Chen; Huai-yang Zhou; Yang Liu; Qun-hui Yang; Ji-wei Li; Henry J.B. Dick (International Geology Review, 2013)

Greenhouse tomato–cucumber yield and soil N leaching as affected by reducing N rate and adding manure: a case study in the Yellow River Irrigation Region China - Ying Zhao; Jiang-Hang Luo; Xiao-Qun Chen; Xue-Jun Zhang; Wei-Li Zhang (Nutrient Cycling in Agroecosystems, 2012)

A meta-analysis of the relationship between glutathione S-transferases gene polymorphism and hepatocellular carcinoma in Asian population - Jie Chen; Liang Ma; Ning-Fu Peng; Shi-Jun Wang; Le-Qun Li (Molecular Biology Reports, 2012)

Expression characteristics of two ubiquitin/ribosomal fusion protein genes in the developing testis, accessory gonad and ovary of Chinese mitten crab, Eriocheir sinensis - Qun Wang; Lili Chen; Ying Wang; Weiwei Li; Lin He; Hui Jiang (Molecular Biology Reports, 2012)

Investigations on serviceability control of long-span structures under human-induced excitation - Xin Chen; Youliang Ding; Zhiqiang Zhang; Peng Sun; Ai-qun Li (Earthquake Engineering and Engineering Vibration, 2012)

XPA A23G polymorphism and lung cancer risk: a meta-analysis - Ji-Hong Zou; Li An; Shi Chen; Li-Qun Ren (Molecular Biology Reports, 2012)

Adaptive evolution of context-dependent style curvature in some species of the Malvaceae: a molecular phylogenetic approach - Cheng-Jiang Ruan; Shi-Chao Chen; Qun Li; Jaime A. Teixeira da Silva (Plant Systematics and Evolution, 2011)

Current evidences on vascular endothelial growth factor polymorphisms and breast cancer susceptibility - Li-Xin Qiu; Ke Wang; Sheng Yang; Chen Mao; Lei Zhao; Lei Yao; Jian Zhang; Qun-Ling Zhang; Si Sun; Kai Xue (Molecular Biology Reports, 2011)

A high-throughput method for screening of Aspergillus niger mutants with high transglycosylation activity by detecting non-fermentable reducing sugar - Gui-guang Chen; Wei Li; Yun-kai Zhang; Yong-ling Qin; Kong-yang Wu; Zhi-qun Liang (World Journal of Microbiology and Biotechnology, 2011)

Differential Gene Expression Analysis of Yunnan Red Pear, Pyrus Pyrifolia, During Fruit Skin Coloration - Xiaodong Zhang; Andrew C Allan; Qiong Yi; Limei Chen; Kunzhi Li; Qun Shu; Jun Su (Plant Molecular Biology Reporter, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake I: Yingxiu town - Chang-Rong He; Ru Zhang; Qun Chen; Sheng-Li Han (Natural Hazards, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake II: Dujiangyan and Pengzhou City - Chang-Rong He; Qun Chen; Sheng-Li Han; Ru Zhang (Natural Hazards, 2011)

Spatial prediction and analysis of Himalayan marmot plague natural epidemic foci in China based on HJ-1 satellite data - MengXu Gao; XiaoWen Li; ChunXiang Cao; Hao Zhang; Qun Li; Hang Zhou; QiSheng He; Min Xu; Jian Zhao; Sheng Zheng; Wei Chen (Science China Earth Sciences, 2010)

Gravity and magnetic anomalies field characteristics in the South China Sea and its application for interpretation of igneous rocks - Shu-Ling Li; Xiao-Hong Meng; Liang-Hui Guo; Chang-Li Yao; Zhao-Xi Chen; He-Qun Li (Applied Geophysics, 2010)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

Unique evolutionary pattern of numbers of gramineous NBS–LRR genes - Jing Li; Jing Ding; Wen Zhang; Yuanli Zhang; Ping Tang; Jian-Qun Chen; Dacheng Tian; Sihai Yang (Molecular Genetics and Genomics, 2010)

Characterization of DUF724 gene family in Arabidopsis thaliana - Xi Cao; Ke-Zhen Yang; Chuan Xia; Xue-Qin Zhang; Li-Qun Chen; De Ye (Plant Molecular Biology, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Apolipoprotein E polymorphism in normal Han Chinese population: frequency and effect on lipid parameters - Shu Liang; Min Pan; Hai-Hua Geng; Hui Chen; Li-Qun Gu; Xiao-Tong Qin; Jin-Jun Qian; Jian-Hua Zhu; Chun-Feng Liu (Molecular Biology Reports, 2009)

Oxidative damage increased in presenilin1/presenilin2 conditional double knockout mice - Dong-Li Zhang; Yi-Qun Chen; Xu Jiang; Ting-Ting Ji; Bing Mei (Neuroscience Bulletin, 2009)

Functional Annotation and Analysis of Expressed Sequence Tags from the Hepatopancreas of Mitten Crab (Eriocheir sinensis) - Hui Jiang; Yi-Mei Cai; Li-Qiao Chen; Xiao-Wei Zhang; Song-Nian Hu; Qun Wang (Marine Biotechnology, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

Numerical simulation on the interaction of an internal solitary wave with a step-type topography - Zhaoting Xu; Qun Li; Xu Chen; Jia Yu (Journal of Ocean University of China, 2008)

Values of endoscopic ultrasonography for diagnosis and treatment of duodenal protruding lesions - Guo-qiang Xu; Yi-qun Wu; Li-jun Wang; Hong-tan Chen (Journal of Zhejiang University-SCIENCE B, 2008)

Total Internal Reflection Fluorescence Spectroscopy for Investigating the Adsorption of a Porphyrin at the Glass/Water Interface in the Presence of a Cationic Surfactant Below the Critical Micelle Concentration - Yao-Ji Tang; Ying Chen; Min-Na Yao; Zhe-Xiang Zou; Guo-Bin Han; Yao-Qun Li (Journal of Fluorescence, 2008)

Fluorescence Spectral Properties of Rhodamine 6G at the Silica/Water Interface - Zhe Chen; Yao-Ji Tang; Tang-Tang Xie; Ying Chen; Yao-Qun Li (Journal of Fluorescence, 2008)

T1 locus in cotton is the candidate gene affecting lint percentage, fiber quality and spiny bollworm (Earias spp.) resistance - Qun Wan; Zhengsheng Zhang; Meichun Hu; Li Chen; Dajun Liu; Xiao Chen; Wei Wang; Jing Zheng (Euphytica, 2007)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

AFLP Analysis of Genetic Diversity of the Endangered Species Sinopodophyllum hexandrum in the Tibetan Region of Sichuan Province, China - Meng Xiao; Qun Li; Liang Guo; Tong Luo; Wen-Xia Duan; Wen-Xing He; Li Wang; Fang Chen (Biochemical Genetics, 2006)

Genetic Diversity and Genetic Structure of an Endangered Species, Trillium tschonoskii - Qun Li; Meng Xiao; Liang Guo; Li Wang; Lin Tang; Ying Xu; Fang Yan; Fang Chen (Biochemical Genetics, 2005)

Soluble Expression and Affinity Purification of Functional Domain of Human Acetylcholine Receptor ?-subunit by the Modulation of Maltose Binding Protein - Zhuo-Yu Li; Yan-Jun Li; Chen-Yun Guo; Ye-Wei Shi; Ming-Qun Xu; Wolfgang E. Trommer; Jing-Ming Yuan (Biotechnology Letters, 2004)